Sociodemographic factors and body image among high school students Fatores sociodemográficos e imagem corporal em adolescentes do ensino médio - Felden E.P.G.* (2015)
© 2015 Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All righrts reserved.The scope of this article is to investigate associations between body image dissatisfaction and sociodemographic indicators among adolescents. Participants included 1126 high school students in the city of Santa Maria in the State of Rio Grande do Sul. Aspects regarding body image dissatisfaction and sociodemographic indicators were analyzed. Association analyses were performed using crude Poisson regression duly adjusted for sex and age. Boys were found to be dissatisfied due to slimness and girls due to excess weight. Adolescents where the parents had less schooling, as well as those from lower socioeconomic classes and with lower income were found to be more likely to have body image dissatisfaction due to slimness. However, those where the parents had completed higher education and those living in the downtown area were more likely to have body image dissatisfaction due to excess weight. Sociodemographic indicators are closely associated with body image dissatisfaction. Body image dissatisfaction due to slimness can be explained by the lower level of schooling of the parents, lower socioeconomic class and lower income. Dissatisfaction due to excess weight can be explained by the higher schooling of the parents and the fact of living in the downtown area.